Preparation and spectroscopic studies of tri(p-tolyl)-tin(IV) compounds. X-ray crystal structure of the quinoline-N-oxide adduct of tri(p-tolyl)tin(IV) bromide - Kumar Das, V.G.; Yap, Chee Keong; Ng, Seik Weng; Chen, Wei (Elsevier, 1986)
Syntheses and spectroscopic data are presented for R3SnIV compounds, where R is predominantly p-tolyl, of the following types: R3SnX·L (X = Cl, Br or NCS; L = neutral, monodentate oxygen donor), R3SnY (YH = 1,2,4-triazole, N-phenyl-N-benzoylhydroxamic, succinanilic, levulinic and hippuric acids) and [R3SnL2]+ [Ph4B]− (L = neutral, monodentate or 1/2 bidentate oxygen donor). The spectroscopic data (IR and Mössbauer) are interpreted in terms of discrete or weakly polymeric trigonal bipyramidal structures, with the R3Sn skeleton forming the equatorial plane for most of the compounds. A cis-geometry is inferred for the case where the anionic residue is the chelating N-phenyl-N-benzoylhydroxamate ligand, while a meridional geometry is predicted for the cationic complexes involving the chelating ligans, 2,2′-bipyridine N,N′-dioxide and ethylenebis(diphenylphosphine oxide). Both the 13C NMR and the IR data suggest that the Lewis acceptor strength falls in the order (p-ClC6H4)3Sn > (C6H5Sn> (p-MeC6H4)3Sn. Crystals of (p-tolyl)3SnBr· quinoline-N-oxide are triclinic, space group P, with a 10.245(4), b 10.862(2), c 13.153(5) Å, α 84.10(2), β 68.39(3), γ 80.88(3)°. The structure was refined to R = 0.070 for 4548 observed Mo-Kα reflections and comprises independent, non-interacting molecules which are pentacoordinate at tin. The quinoline-N-oxide ligand is coordinated apically to tin in the trigonal-bipyramidal unit; the three tolyl rings occupy the trigonal plane but the tin atom is displaced by 0.17(1) Å towards the other apical bromide ligand.